2013
DOI: 10.2337/dc12-0445
|View full text |Cite
|
Sign up to set email alerts
|

Extended Family History of Type 1 Diabetes and Phenotype and Genotype of Newly Diagnosed Children

Abstract: OBJECTIVETo determine the frequency of newly diagnosed diabetic children with first- and second-degree relatives affected by type 1 diabetes and to characterize the effects of this positive family history on clinical markers, signs of β-cell autoimmunity, and HLA genotype in the index case.RESEARCH DESIGN AND METHODSChildren (n = 1,488) with type 1 diabetes diagnosed under 15 years of age were included in a cross-sectional study from the Finnish Pediatric Diabetes Register. Data on family history of diabetes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
83
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 33 publications
8
83
0
4
Order By: Relevance
“…To further characterize the effects of a positive family history of AIDs, we grouped the index children into autoimmune families, in which autoimmunity was truly clustered, and accordingly, differences in pathogenetic mechanisms should be evident. The only significant difference observed, however, was the milder metabolic decompensation at diagnosis among the children from autoimmune families, which is probably due to the effect of familial diabetes and the earlier recognition of symptoms in such families (29). These findings do not consistently support the hypothesis of different pathogenetic mechanisms of diabetes operating in families with clustered autoimmunity.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…To further characterize the effects of a positive family history of AIDs, we grouped the index children into autoimmune families, in which autoimmunity was truly clustered, and accordingly, differences in pathogenetic mechanisms should be evident. The only significant difference observed, however, was the milder metabolic decompensation at diagnosis among the children from autoimmune families, which is probably due to the effect of familial diabetes and the earlier recognition of symptoms in such families (29). These findings do not consistently support the hypothesis of different pathogenetic mechanisms of diabetes operating in families with clustered autoimmunity.…”
Section: Discussionmentioning
confidence: 61%
“…This could reflect the increased genetic risk of autoimmunity in the relatives of mothers or a recollection bias in the form of mothers being more aware than fathers of the diseases diagnosed in their relatives. Interestingly, in the same dataset, such a difference was not observed for T1D; it was reported equally often in maternal (6.5%) and paternal (6.0%) second-degree relatives, but was more common in fathers (6.2%) than in mothers (3.2%) (29). This emphasizes the differential sex distributions and possible sex-dependent inheritance patterns in T1D and other AIDs.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…A recent study on the Finnish population [2] reported that 12.2 % of the newly diagnosed T1DM children had a 1st degree relative with T1DM and 11.9 % had an affected 2nd degree relative. Children without affected relatives had lower pH, higher plasma glucose and a higher rate of impaired consciousness, and more relevant weight loss at T1DM onset.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention proved to have no effect on the progression to T1D (13). Cases with T1D were diagnosed by the World Health Organization (WHO) criteria (14) and ascertained from the patient records of the University Hospitals of Turku, Oulu, and Tampere, and from the National Diabetes Register (15). Follow-up for T1D continued until the end of October 2012.…”
Section: Subjects and Study Designmentioning
confidence: 99%